PROVISION OF DENTAL CARE TO THE POPULATION OF UKRAINE: 15-YEAR DYNAMICS AND CURRENT PROBLEMS - L.I. Artemchuk; L.О. Lytvynova; О.M. Donik; K.V. Orlychenko (Український стоматологічний альманах)
Providing the population of Ukraine with qualified dental care is an important component of the general health of the nation. Dental services not only contribute to the prevention and treatment of oral diseases, but also have a great impact on the general health, quality of life and social activity of citizens. In modern conditions, when access to medical services is becoming one of the main problems, it is important to assess the level of provision of the population with dental care, analyzing existing problems and ways to solve them.